1987
DOI: 10.1007/bf00436848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roasting on ochratoxin A level in green coffee beans inoculated with Aspergillus ochraceus

Abstract: The heat stability of ochratoxin A in green coffee beans inoculated with Aspergillus ochraceus was studied. Heat treatment (roasting) at 200 degrees C for 10 or 20 min reduced the levels of ochratoxin A by only 0-12% in the dried whole beans. Almost all of the ochratoxin A was infused into the coffee decoction when the roasted samples were ground and extracted with boiling water. Therefore, the reduction of ochratoxin A concentration of contaminated coffee beans by roasting under these conditions is ineffectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 12 publications
3
71
0
1
Order By: Relevance
“…Several studies have been published regarding the heat stability of OA during the roasting process. Tsubouchi et al (1987) reported a reduction of 0-12 % OA after roasting artificially inoculated beans contaminated in the range of 200 to 140,000 #g/kg, which corroborates our own findings. One can assume a relatively high homogeneity in artificially contaminated samples as indicated by the results presented here, although Tsubouchi et al (1987) did not report corresponding data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have been published regarding the heat stability of OA during the roasting process. Tsubouchi et al (1987) reported a reduction of 0-12 % OA after roasting artificially inoculated beans contaminated in the range of 200 to 140,000 #g/kg, which corroborates our own findings. One can assume a relatively high homogeneity in artificially contaminated samples as indicated by the results presented here, although Tsubouchi et al (1987) did not report corresponding data.…”
Section: Discussionsupporting
confidence: 91%
“…While only isolated data exist regarding nuts, dates, soya beans and cocoa beans, the natural occurrence of OA in green and roasted coffee beans has been reported several times. However, inconsistent results have been published with respect to the influence of the roasting process on the OA content (Gallaz and Stadler, 1976;Micco et al, 1989;Tsubouchi et al, 1987) and the transfer of OA into the brew (Micco et al, 1989;Tsubouchi et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Tsubouchi et al (1987) found thut after Inoculation with A.~, roasting green coffee beans for 20 min at 2lXJOC reduced the concentration ofOTA by a maximum of only 12% in whole beans and 18·22% in ground beans. They concluded that the mode of OTA contamination wa.~the reason for Ihis greater heat resistance.…”
Section: Stability Of Ota and Dfccts Of Food Processingmentioning
confidence: 92%
“…The first report on the occurrence of OTA in coffee appeared in 1974 [98]. Since then, several reports have confirmed the presence of OTA in green coffee beans [99][100][101][102], roasted coffee [103,104] and instant coffee [105,106]. OTA has also been detected in the final coffee brew prepared under normal methods [107].…”
Section: Occurrence Of Ota In Coffeementioning
confidence: 99%